Mídias de massa e redes sociais : desordem informacional e violação de privacidade - Almeida, Ricardo Nery de (2020)
This work aims to contribute to studies related to the mechanisms of content production and distribution, manipulation and control by mass media (press, TV, radio) and social networks, and the effects caused by information disorder and privacy violation. We have chosen as theoretical sources for the research the works of Critical Theory with contributions of Herbert Marcuse and Douglas Kellner, the studies of media of Neil Postman and Marshall McLuhan, and works in the area of Digital Culture. The possibility of damaging individuals, institutions or even affecting democratic systems was demonstrated by making use of Floridi's notion of “semantic information”, in order to clarify the notion of “informational disorder”. When addressing the use of algorithms in the authorized and unauthorized capture of sensitive and non-sensitive data from users and non-users of social networks, the risks related to the violation of privacy, production of socio-political vulnerability and mechanisms of control as well as the impacts of the massive use of technologies in the digital environment, on democracies. To this end, we carried a bibliographic survey in search of the necessary sources for the theoretical basis. It is hoped that the results presented will contribute to the theme being more debated, promoting more scientific studies in the area.